Peningkatan Keterampilan Passing Bawah Bola Voli Melalui Model Pembelajaran Jigsaw Pada Siswi Kelas Ix-J Mtsn 4 Jombang - faruk, umarul (Balai Diklat Keagamaan Surabaya, 2021)
This study aims to improve the mastery of the concept of passing down volleyball for class IX-J students at MTsN 4 Jombang in the 2019/2020 school year. The subjects of this study were students of class IX-J MTsN 4 Jombang in the 2019/2020 school year. The design of this research is that this research is a classroom action research so that the research design used in this study is a design of classroom action research (CAR). The research instrument consisted of learning observation sheets and student test sheets. The data from this study were analyzed using the formula for the average percentage score of the results of the research instrument. The results of this study indicate that there is an increase in the average value of student learning outcomes from each research cycle, with details of the average score in the first cycle of (73.33%), the second cycle (86.66%), and the third cycle (96.66%). . The conclusion of this study is that the jigsaw learning model has the potential to improve the mastery of the concept of passing under volleyball for class IX-J MTsN 4 Jombang students in the 2019/2020 school year.